Spiritual Needs and Resilience Women with Cervical Cancer - Supatmi Supatmi; Fathiya Lutfil Yumni; Reliani Reliani; Diah Priyantini (Babali Nursing Research)
Introduction: Spiritual needs are crucial in providing support for cervical cancer patients in palliative care. Spiritual support helps reduce feelings of despair and depression, enabling patients to undergo treatment and maintain their quality of life. Resilience refers to individual characteristics that are adaptable and support successful coping with cancer. This study aimed to examine the spiritual needs and resilience of women with cervical cancer.